The Two ’Greek Buddhas’ - Dimou, Nikos (Conatus - Journal of Philosophy, 2022)
This article discusses the influence of Indian Buddhism on Greek Skepticism and their philosophical method of stress management through the Greek philosopher Pyrrho of Elis. That influence was the subject of two books with similar titles mentioning the “Greek Buddha,” as Pyrrho was called by Nietzsche. Both books, one written in Greek from a layman’s perspective approximately 40 years ago and one written in English from a scholarly perspective approximately 6 years ago, discussed the similarities of the Eastern and Western traditions in terms of the goal of serenity, ataraxia. The book published in 1984 was the first one in Greece to link Greek Hellenistic Philosophy to Oriental Wisdom and especially to the early Philosophy of Buddhism. Both traditions offer a practical way of philosophical management of everyday stress and suffering through the mentality of suspension of judgement and non-attachment to certainties.